The prognostic value of neutrophil-to-lymphocyte ratio in nasopharyngeal cancer - Mustafa Kandaz; Atalay Balsak; Hatice Bengü Çobanoğlu (Northwestern Medical Journal)
Introduction: The prognostic value of the neutrophil-to-lymphocyte ratio (NLR) for nasopharyngeal carcinoma (NPC) continues to be debated. This study was conducted to enhance the accuracy of its prognostic value through a single-centre analysis.